Rusų formalizmas ir anglų bei amerikiečių naujoji kritika - Gornykh, Andrei (Problemos, 2004)
The problem of the General and the Particular seems to be the pure philosophical one. The Notion or Idea seems to be the privileged and self-sufficient subject of reflection. The article outlines the possibility to place these problems simultaneously in aesthetical and social-anthropological perspectives thus revealing something like the genealogy or background of the metaphysical preoccupation with the Unity and Multiplicity.